BMP-2 Expression of Post Tooth Extraction that Catfish Oil Application - B., Theresia Indah; Sumaryono, Bambang; Suardita, Ketut; R., Amelia Putri (KnE Life Sciences, 2017)
Catfish (Clarias batrachus) oil contain the highest amount of omega-3-PUFA among other freshwater fish. The omega-3-PUFA in fish oil produced eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). It is known that EPA and DHA in essentials fatty acid (EFA) could improve BMP-2 expression. Bone morphogenetic protein-2 (BMP-2) is bone stimulator which capable of inducing differentiation of mesenchymal cells into osteoblast, stimulating bone formation in wound healing process of dental extraction. Purpose: To prove the increasing expression of BMP-2 after catfish (Clarias batrachus) oil application. Methods: We have used the post test only design in this research. There have been 21 Rattus novergicus as research samples, and those were divided into 3 groups, group KK as control, group KP1 was given catfish (Clarias batrachus) oil in 5% concentration, and group KP2 was given catfish (Clarias batrachus) oil in 10% concentration. Catfish (Clarias batrachus) oil were applied into the socket of dental extraction. Rat was decapulated 7 days after fish oil application and the jaw in the treated regions and control group were cut for immunohistochemistry examination to observe BMP-2 expression. Data was analyzed using one-way ANOVA test. Result: There is significant difference increased of BMP-2 expression between control and treatment group. In samples given with 10% concentration of catfish oil had the most significant increase of BMP-2 expression. Conclusion: Catfish (Clarias batrachus) oil in 10% concentration could increase the expression of BMP-2 post dental extraction. Key words: Catfish oil, BMP-2, dental extraction.